flipkart.com’s Strategy on Amazon.com’s Entry into India :A Case Study - B, Padmanabh (Ushus Journal of Business Management, 2021)
The online retail industry in India is expected to grow to Rs. 7000 crores by 2015. Its size in 2013 is Rs. 2500 crores. By 2014 India is expected to become the 3rd largest nation of Internet users and this would provide huge potential to the online retail Industry1.Among the major cities in India, consumers in Mumbai topped the chart in doing online shopping followed by Ahmedabad and Delhi2. As per Google study conducted in 2012, 51 percent of the traffic for its Great online shopping festival (GOSF) was due to customers from cities other than the four metros. Referring to the growth in online sales, Nitin Bawankule, industry director, e-commerce, online classifieds and media/entertainment at Google India said, “Top motivators for shopping online include cash back guarantee, cash on delivery, fast delivery, substantial discounts compared to retail, and access to branded products”3. The E –commerce space in India has seen a lot of action and there are many online players like flipkart.com, Myntra.com, Fabmart, Indiaplaza and Indiatimesshopping. Amazon.com made an indirect entry through Junglee.com. The reason for this indirect entry is the result of government policy towards foreign direct investment. The Government of India announced in September 2012 the revised foreign direct investment policy in retail. As per this announcement foreign investments are blocked in e-commerce sector while allowing 51 percent FDI in multi-brand retail stores and 100 percent FDI in single brand retail. Amazon has been eyeing the Indian E commerce market which is estimated around 2 billion4.